Strengthening Technology for Damaged Floor Slabs through Compression Zone Enlargement and External Reinforcement - Kalmykov, Oleg; Psurtsieva, Nina; Binkevych, Kostiantyn (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article presents a technology for strengthening reinforced concrete floor slabs by enlarging the compressed zone and using external reinforcement. A 50 mm-thick monolithic overlay is installed on top of the slab, while steel channels are anchored below using chemical fasteners. The slab is pre-leveled with jacks; after hardening, the beams are removed. Full-scale hydrostatic tests confirmed the restored load-bearing capacity and minimal deflections (~2 mm). The method eliminates the need for dismantling, accelerates reconstruction, reduces costs by up to 58%, and preserves interior geometry - making it highly suitable for restoring war-damaged residential buildings.
Keywords: floor slab strengthening; reinforced concrete overlay; external reinforcement; chemical anchors; load-bearing capacity; building rehabilitation